Silicone Oil Tamponade for Therapy of Primary Retinal Detachment in Patients Who Live at High Altitudes - Beltraminelli, Tim; Hessler, Quentin; Stappler, Theodor; Potic, Jelena; Wolfensberger, Thomas J.; Konstantinidis, Lazaros (Klinische Monatsblätter für Augenheilkunde, 2024)
Background Uncomplicated rhegmatogenous retinal detachment (RRD) is mainly treated with vitrectomy and gas tamponade or, alternatively, scleral buckling surgery. However, gas tamponade inflates at high altitudes, causing significant complications. Silicone oil (SO) tamponade volume is unaffected by atmospheric pressure and may be used in patients who live or must undertake travel at high altitudes.Purpose To determine the anatomical and functional outcomes after pars plana vitrectomy (PPV) with SO tamponade in primary uncomplicated RRD.Methods Twenty-eight consecutive cases of patients operated between January 2017 and December 2022 in Jules-Gonin University Eye Hospital in Lausanne were included in this retrospective study. All patients had a follow-up of at least 3 months after SO removal.Results Primary reattachment was achieved in all 28 eyes. Mean follow-up was 17.2 months (range: 3 – 51 months) after SO removal. Mean age at the time of intervention was 60 years (range: 21 – 80 years). Vision was stabilized or improved in 27 eyes (96%). One patient demonstrated a slight visual acuity decrease due to cataract formation at the last follow-up. In all patients, SO was removed 2 to 5 months after primary repair. In 14 of the 21 phakic patients, concomitant cataract surgery was performed. No surgical complications were encountered. Postoperatively, 5 (18%) patients had ocular hypertension, presumably steroid related, that was successfully controlled with topical treatment.Conclusion PPV with SO injection seems to be a safe and efficient surgical approach in the treatment of primary uncomplicated RRD in patients living at high altitudes and was associated with good anatomical and functional outcome in our series. However, the need for a follow-up surgery to remove SO should be weighed in these cases.
Keywords: retinal detachment surgery; silicone oil; uncomplicated detachment; vitrectomy